TRANSFORMASI MEDIA SOSIAL SEBAGAI PUSAT EDUKASI VISUAL: STRATEGI KEWIRAUSAHAAN PENDIDIKAN UNTUK KEBERLANJUTAN KOMUNITAS BELAJAR - Afroh Rozana; Anggun Setiani; Syfa Maulidiyah; Baihaqi; Ferida Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation has transformed social media from a mere means of communication into an educational space with great potential in supporting the sustainability of learning communities. However, the use of social media as a center for visual education still faces various obstacles, such as low digital literacy, weak content management strategies, and a lack of integration between educational and entrepreneurial aspects. This study aims to analyze the strategy for transforming social media as a center for visual education through an educational entrepreneurship approach to support the sustainability of learning communities in the digital era. The method used is a literature study by reviewing various scientific journals, books, and relevant academic sources. Data were analyzed using qualitative content analysis techniques to gain a comprehensive understanding of the relationship between digital transformation, educational management, entrepreneurship, and the use of social media. The results of the study indicate that the success of transforming social media as a center for visual education is determined by strengthening digital literacy, implementing an entrepreneurial mindset, technology-based learning innovation, managing engaging visual content, and supporting adaptive educational policies and management. The integration of digital technology, educational entrepreneurship, and visual communication strategies can increase community participation, strengthen the sustainability of learning communities, and create a more innovative, inclusive, and competitive educational ecosystem in the digital era.